The guardians of plant genetic resources - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
During the armed conflict in Somalia in the mid-1990s, the national germplasm collection was destroyed along with the crops in the fields. At the request of the Somali government, a collector of the International Plant Genetic Resources Institute...